THE INFLUENCE OF AGE, ANOTHER COMPLICATION AND TYPES OF LABOR WITH NEWBORN ASPHYXIA ON SEVERE PREECLAMSIA EXPECTANT AT RSUDP MATARAM IN 2013-2014 - St. Halimatusyaadiah St. Halimatusyaadiah; Irmayani Irmayani (Jurnal Kesehatan Prima, 2016)
Abstract: One of the causes of expectant mother and fetus’ morbidity and mortality is severe preeclampsia and asphyxia in newborns. Asphyxia in newborns is the first cause of infant death in Indonesia, and the second cause of infant death after Low Weight Birth in West Nusa Tenggara province. This research was conducted in the delivery room of RSUDP NTB which aimed to determine the effect of age, another complication and types of birth with newborn asphyxia to mother who suffers severe preeclampsia. The collection of secondary data is obtained by searching delivery room registration and patients’ medical record at RSUDP NTB. The research design used in this study was observational analytic with cross sectional design, sample in this study  were all birth mothers with severe preeclampsia who delivered  alive single newborn, and  were recorded at delivery room registration and medical records of RSUDP NTB in 2013 and 2014  was 111 cases. The analysis was logistic regression. Based on the results of the study, it can be percieved that 111 expectant mothers with severe preeclampsia, the most types of deliveries were cesarean section (SC) as many as 55.9%, and the babies who were born do not suffer asphyxia (73%). Variables which connected and affected to the incidence of asphyxia is the kind of labor with the asphyxia newborn on severe preeclamsia mothers at RSUDP NTB years 2013-2014 with p value = 0.003 and OR = 4.623